2021
DOI: 10.1155/2021/8849131
|View full text |Cite
|
Sign up to set email alerts
|

T0901317, an Agonist of Liver X Receptors, Attenuates Neuronal Apoptosis in Early Brain Injury after Subarachnoid Hemorrhage in Rats via Liver X Receptors/Interferon Regulatory Factor/P53 Upregulated Modulator of Apoptosis/Dynamin‐1‐Like Protein Pathway

Abstract: Background and Purpose. T0901317, a liver X receptor (LXR) agonist, is widely used to explore the functions of LXRs. T0901317 exerts antiapoptotic effects in many central nervous system disease models. Our aim was to detect the role of T0901317 in neuronal apoptosis in early brain injury after subarachnoid hemorrhage. Methods. Subarachnoid hemorrhage (SAH) models of Sprague-Dawley rats were established with perforation method. T0901317 was injected intraperitoneally 1-hour post-SAH. GSK2033, an inhibitor of LX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In the present study, activation of the RARα promoted M1-to-M2 phenotypic polarization of microglia in an in vitro model of SAH. Apoptosis, as an important regulatory mechanism of cell death, is involved in the pathological processes underlying many diseases ( 46 , 47 ). Activation of the RARα with Am80 significantly suppressed neuronal apoptosis after SAH; this was consistent with previous research ( 14 ) and suggests that the activation of RARα attenuates the neurotoxic effects of activated microglia by suppressing the production of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, activation of the RARα promoted M1-to-M2 phenotypic polarization of microglia in an in vitro model of SAH. Apoptosis, as an important regulatory mechanism of cell death, is involved in the pathological processes underlying many diseases ( 46 , 47 ). Activation of the RARα with Am80 significantly suppressed neuronal apoptosis after SAH; this was consistent with previous research ( 14 ) and suggests that the activation of RARα attenuates the neurotoxic effects of activated microglia by suppressing the production of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has revealed that oxidative damage and inflammatory response play critical roles in the pathogenesis of SAH [ 25 29 ]. Diminishing oxidative damage and inflammatory response could significantly improve neurological outcome after SAH [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modified Garcia score and the beam balance score were used to assess the short-term neurological function 24 h after SAH. The modified Garcia score was divided into six categories as follows: Voluntary movement, voluntary limb movement, forepaw extension, climbing ability, somatosensory responses and tentacle response, each of which was scored individually and summed to give a total score ranging from 3–18 ( 25 ). Higher scores were considered to indicate better neurological function.…”
Section: Methodsmentioning
confidence: 99%